2020
DOI: 10.1007/s00213-019-05450-6
|View full text |Cite
|
Sign up to set email alerts
|

Paternal morphine self-administration produces object recognition memory deficits in female, but not male offspring

Abstract: Rationale: Parental drug use around or before conception can have adverse consequences for offspring. Historically, this research has focused on the effects of maternal substance use on future generations but less is known about the influence of the paternal lineage. This study focused on the impact of chronic paternal morphine exposure prior to conception on behavioral outcomes in male and female progeny. Objectives: This study sought to investigate the impact of paternal morphine self-administration on anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 94 publications
2
20
0
Order By: Relevance
“…A major advantage of the task is that it can be used in both rats and mice (Agarwal et al, 2020;Chang et al, 2020). Current iterations of the NOR paradigm are widely used to study memory (Cole et al, 2020), synaptic plasticity (Lee et al, 2020), impairment and/or recovery of function in brain disease (Grayson et al, 2015), TBI (Amoros-Aguilar et al, 2020), stress (Brivio et al, 2020;Glushchak et al, 2021), aging (Amirazodi et al, 2020), sleep (Shahveisi et al, 2020), autism (Batista et al, 2019;Gandhi and Lee, 2020), and epigenetics (Ellis et al, 2020;Sadat-Shirazi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A major advantage of the task is that it can be used in both rats and mice (Agarwal et al, 2020;Chang et al, 2020). Current iterations of the NOR paradigm are widely used to study memory (Cole et al, 2020), synaptic plasticity (Lee et al, 2020), impairment and/or recovery of function in brain disease (Grayson et al, 2015), TBI (Amoros-Aguilar et al, 2020), stress (Brivio et al, 2020;Glushchak et al, 2021), aging (Amirazodi et al, 2020), sleep (Shahveisi et al, 2020), autism (Batista et al, 2019;Gandhi and Lee, 2020), and epigenetics (Ellis et al, 2020;Sadat-Shirazi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rat offspring derived from female and male parents treated with morphine exhibit memory deficiency that is presumably because of suppression of long-term potentiation in the hippocampus ( Sarkaki et al, 2008 ). Paternal exposure of Sprague Dawley rats to morphine impairs novel-object recognition in female but not male progeny ( Ellis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These changes were not seen in the female F1 and F2 progeny, suggesting sex-specific alterations resulting from maternal adult morphine exposure. Ellis et al have also shown that paternal morphine exposure produces sex-specific impairments in object recognition memory in female offspring [72]. Additionally, offspring born to parents with adult morphine exposure had decreased object recognition, possibly due to decreased histone H3 acetylation and ∆FosB levels in the PFC and hippocampus [73].…”
Section: Morphinementioning
confidence: 97%